OPTIMIZATION OF SERVICE AND INCREASED PDAM INCOME THROUGH DEVELOPMENT OF CLEAN WATER DISTRIBUTION CAPACITY IN HIGH PURCHASING AREAS (CASE STUDY DISTRICT OF WEST AND SOUTH PEKALONGAN) - ROSMAYASARI , MULIANI
Abstract: PDAM Pekalongan City is a company that has a dual function which is as a profit oriented and public service company where both functions must be able to achieve balance because it has a close causality relationship in maintaining the existence of the business being run. The additional 150 l/s water supply that will be obtained by PDAM in 2019 from the Regional SPAM Petanglong is an opportunity for companies to increase service scale through the development of distribution channel networks while increasing PDAM revenues. One effort that can be done is by developing clean water distribution capacity in areas with high purchasing power. From the results of a survey conducted on 285 respondents, non- commercial customers in the 10 urban villages that were targeted for development, 38.25% of respondents were interested in becoming PDAM customers. The selection of the optimization target area based on Break Even Point (BEP) parameters shows Pringrejo, Tirto, Medono, Buarankradenan, Pasirkratonkramat, Jenggot, Banyurip and Bendankergon villages are areas that provide BEP faster than 8 years. Optimization analysis shows that the results of clean water capacity needed for optimization of commercial groups in high purchasing power areas are 2.1 l/s from 150 l/s of additional capacity received by the PDAM. Development of clean water distribution capacity in high purchasing power areas can increase PDAM revenue by IDR 604,610,84 in a year with an increase in profit margin of 1.25% compared to before the development. Economic analysis based on BCR analysis obtained BCR>1 value, positive NPV value and IRR value bigger than MAR which means the project is declared feasible to be implemented.